The Implementation of Green Accounting Based on University Social Responsibility (USR) With Independent Test - Dwi Suhartini; Astrini Aning Widoretno; Invony Dwi Aprilisanda; Rizdina Azmiyanti (Future Science, 2021)
This study aims to analyze the implementation Green Accounting based on University Social Responsibility (USR) in University. A systematic literature review is conducted from database with “university social responsibility” as the keyword. The articles were further filtered to specific literature that refer to the implementation of social responsibility with independent t-test and statistical test. Most of USR research used qualitative method. This literature review will understand the USR implementation with 4 dimensions consist of environmental awareness, environmental involvement, environmental reporting, and environmental auditing. The universities across the world need to be aware about environment for sustainability and the implementation of sustainability development goals in 2030. The finding articles can be explained from English and Indonesia sources. Relevant articles will be developed to understand the USR concept for improving the research scope.